The platformization of consumer culture: A theoretical framework - Caliandro, Alessandro; Gandini, Alessandro; Bainotti, Lucia; Anselmi, Guido (Marketing theory, 2024)
This special issue, together with this position paper that accompanies it, aims at providing a comprehensive framework to address this issue, introducing and theorizing the concept of platformization of consumer culture. The overarching scope of this essay is to discuss what is distinctive of the process of platformization in relation to consumer culture (and research); what are its most important aspects, its critical controversies, its innovative dimensions and main risks. Accompanying this positional essay are the seven exceptional contributions that compose the special issue, which we believe will come to represent a pivotal reference in the quest to address this phenomenon. These showcase the manifold empirical, semantic and methodological dimensions of this emergent phenomenon, concurring to define the key dimensions that identify, describe, and explore the ways in which consumer culture has been “platformized,” from the perspective of consumer culture theory. Specifically, we identify four key “tensions” characterizing the platformization of consumer culture: datafication vs liquification; standardization vs ephemerality; interaction vs mediation; immateriality vs materiality.